The Impact of the Dormitory Duty Policy on Improving Student Discipline at Madrasah Muallimin Muhammadiyah Yogyakarta - Hastuti, Dwi; Nafia, Zidni Ilma (Journal of Indonesian Progressive Education, 2024)
The dormitory administrators' concerns about the cleanliness of the dormitory, which is not clean, can cause the spread of disease. This study aims to examine how the management of the dormitory duty policy implemented at Madrasah Muallimin Muhammadiyah Yogyakarta can improve the discipline of students. This study uses a qualitative method with a field research type. The data obtained came from observation, interviews, and documentation. The results of this study indicate that the dormitory duty policy can improve the discipline of students. In addition, the impact of the policy is also able to make all parties in the dormitory submit and comply with its policies. The dormitory administrators can improve their skills in planning, organizing, directing, and controlling. While the students who improve their discipline, character, responsibility, moral attitude, and skills. With the presence of this dormitory duty, the dormitory becomes clean, and the scabies suffered by the students are reduced.